ARS DISPUTANDI UND RHETORIK IN FRÜHNEUZEITLICHER DISPUTATIONSLITERATUR DES OSTSEERAUMS - Marti, Hanspeter (Gerundium, 2021)
The introduction to this article focuses firstly on the upturn in disputation research during the last two decades. This increase in interest was helped a lot by digitisations, not only of library catalogues but also of a large number of entire Early Modern dissertations. The second focus of the introduction lies on scriptures about the important neighbouring disciplines of logic and rhetoric and their relation to each other. The following chapters revolve around the disputation culture of the 17th and 18th century at the universities of Greifswald, Rostock and Königsberg (Kaliningrad), as well as the “Athenäum” of Gdansk. Each of these four schools had its own peculiarities: in Greifswald it was the episodic use of the German language in dissertations, in Rostock it was notable that there were many juridical programs on the “disputatio”, while the texts from Gdansk stood out with their numerous large appendices containing congratulatory texts and even poems. Lastly, Königsberg stood out with its wide spectrum of disputation literature within the philosophic faculty.